La révolution électrique en cours : portrait de l’émergence d’une nouvelle architecture dans les pays industrialisés - Phillip U. Dunsky (VertigO)
In the short and medium terms, the precise architecture of the industrial world’s electricity system remains hazy. Yet in the long term, it seems quite clearly headed toward a new configuration, rooted in a triad of solid trends: miniaturization, decentralization and the “greening” of power generation. This text describes and explains these trends and their underlying forces, namely the combined effects of technological progress, growing environmental consciousness, the advent of a digital economy and the opening of markets to competition.